"What Is Truth?" Negotiating Christian Convert Asylum Seekers' Credibility. Issue 1 (September 2021) - Rose, Lena; Given-Wilson, Zoe
The arrival of more than five million refugees in Europe since 2015 has led to increasing investigations into Europe's management of multiculturalism and religious pluralism. Studies to date have chiefly focused on the integration of the cultural and religious "other, " but we take a different approach by analyzing asylum proceedings in Germany, based on conversions from Islam to Christianity. Negotiations of credibility of newly converted Christian asylum seekers help to show how European legal authorities conceive of their own historically Christian identity and their expectations of newcomers. We show how these negotiations are influenced by the power dynamics in the courts, understandings of cultural and religious contexts, and assumptions about conversion and Christianity. Our interdisciplinary approach provides insights into how European legal authorities navigate the challenge of cultural and religious others to Europe's cultural cohesion, "values, " and secularism.